MORPHOLOGICAL AND ANATOMICAL STUDY OF THE GRASS OF VERONICA SPICATA L. - A. V. Kovalyova; A. S. Nikitina (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
The article presents the results of morphological and anatomical studies of Veronica spicata L. Macro- and microscopic features of the grass of Veronica spicata were described. We have determined the principal diagnostic features of leaves and stems of the plant's active parts. We have found two types of trichomes in active parts of Veronica spicata L.: simple pluricellular fuzz and cephalated glandular fuzz with monocellular pedicle and monocellular or bicellular sphere-like capitulum, anomcytic stomatal apparatus.